Car Security Alarm / Noor Irmahani Mohmad Tahiruddin and Shazwani Mohd. Ismail - Mohmad Tahiruddin, Noor Irmahani; Mohd. Ismail, Shazwani (2005)
Car Security Alarm is a security system designed to detect car theft using switch as a mode of sensing The main purpose of accomplishing this project is to outcome with a new device to detect break-ins of car theft. In order to complete this project, there are several programs that could be used We decided to finish up our project using the PCB Designer to come out with the PCB Designer Piezo buzzer sounds when the car door is opened (black wire connected to ground). When door is closed (black wire is disconnected), the capacitor is discharged. Then, when the door is reopened (black wire is reconnected), the horn will sound. The expenses for this project came up lo a total of RM30.65. The project is considered successful, yet need some improvisations and adjustments. This are probably due to the components that are unable to function properly. This proposed project will provide a better life comfort and an environment free from thieves.